Penerapan Asas Hakim Aktif (Dominus Litis) dalam Persidangan di Pengadilan Tata Usaha Negara (Studi Kasus Putusan No.1/G/2017/PTUN.DPS.) - Ni Komang Dewi Novita Indriyani Weda; I Made Arjaya; I Putu Gede Seputra (Jurnal Preferensi Hukum, 2021)
In the judiciary the Judicial State Administration plays a more active role in the trial process in order to obtain material truth. The activist of the judge is intended to compensate for the unequal position of the parties, namely the Defendant is an entity or official of the State administration and the Plaintiff is an individual or civil legal entity. In this research there are two main problems, namely (1) how is the Procedure for Making a Gathering in the State Administrative Court? (2) How is the application of the principle of active judge (dominus litis) in the stage of proof at the trial? The research method used is normative legal research with a legal approach.